Specific Aspects of Neurophysiological and Neuroimaging Study of Multiple Sclerosis Patients with Spasticity - Domres, Nataliia; Sokolova, Larysa (IJRDO -JOURNAL OF HEALTH SCIENCES AND NURSING, 2020)
The objective of the study was to assess the functional state of muscle fibers in spasticity and prognostic value of the number and localization of MRI lesions for its development in MS patients. Material and methods. We studied findings of electroneuromyography in 51 multiple sclerosis patients with spasticity. The study was performed using non-invasive stimulation technique with a Nihon Kohden device. Results. In patients with MS with minimal clinical signs of spasticity, a significant decrease in the amplitude of the M-response was revealed when examining both the upper and lower extremities. Indicators of late electrophysiological phenomena (F-wave) changed only in the lower limbs, where the level of spasticity was higher. We identified threshold levels of M-amplitude to assess the risk of developing a high spasticity score of >12. The number of T2 and T1 lesions, as well as their localization in the spinal cord, have prognostic value for early development of spasticity. Conclusion. The results of the study revealed the main electrophysiological indicators of early manifestations of spasticity in MS patients and prognostic value of the number and localization of MRI lesions.